Higher Educational Attainment Associated with Optimal Antenatal Care Visits among Childbearing Women in Zambia - Muyunda, Brian; Makasa, Mpundu; Jacobs, Choolwe; Musonda, Patrick; Michelo, Charles (Frontiers in Public Health, 2016)
Objective Attendance of at least four antenatal care (ANC) visits over the period of pregnancy has been accepted by World Health Organization to comprise the optimal and adequate standard of ANC because of its positive association with good maternal and neonatal outcomes during the prenatal period. Despite free ANC being provided, many pregnant women have been found not to meet this minimum number of ANC visits in Zambia. We investigated if educational attainment is associated with optimal ANC visits among childbearing women in Zambia. Methods Data stem from the 2007 Zambia Demographic and Health Survey for women, aged 15–49 years, who reported ever having been pregnant in the 5 years preceding the survey. The linked data comprised sociodemographic and other obstetrical data, which were cleaned, recoded, and analyzed using STATA version 12 (Stata Corporation, College Station, TX, USA). Multivariate logistic regression was used to examine the association of educational attainment and other background variables. Results Women who had higher education level were more likely to attend at least four ANC visits compared to those with no education (AOR 2.8, 95% CI 1.51–5.15; p = 0.001); this was especially true in the urban areas. In addition, women with partners with higher education level were also more likely to have optimal ANC attendance (OR 2.0, 95% CI 1.3–3.1; p = 0.002). Conclusion Educational attainment-associated differentials found to be linked with optimal ANC attendance in this population suggests that access to health care is still driven by inequity-related dynamics and imbalances. Given that inequity stresses are heaviest in the uneducated and probably rural and poor groups, interventions should aim to reach this group. Significance The study results will help program managers to increase access to ANC services and direct interventional efforts towards the affected subpopulations, such as the young, uneducated, and rural women. Furthermore, results will help promote maternal health education and advise policy makers and program implementers.